2022
DOI: 10.1108/ijchm-06-2021-0772
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the measurement model of a new scale for evaluating restaurant service quality during major infectious disease outbreaks

Abstract: Purpose Consumers prefer to choose restaurants that value hygiene and safety; therefore, appropriate epidemic prevention measures could restore 30% of lost customers and enhance a restaurant’s reputation during infectious disease outbreaks. Providing customers with safe epidemic prevention service quality is an important mission of the restaurant industry during an epidemic. This study aims to construct an epidemic prevention service quality scale for restaurants (REP-SERV scale). Design/methodology/approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…As a result, consumers may place greater value on cleanliness and sanitation and behave in a risk-averse way to avoid health risks. This is consistent with the salience theory of choice under risk (Bordalo et al, 2012;Bordalo et al, 2013) and more recent COVID-19 studies which confirmed that safety has become customers' primary concern (Chang and Cheng, 2022;Kim et al, 2021a). Therefore, this study confirmed the effectiveness of the salience theory under risk in understanding consumers' restaurant choice amid a global pandemic.…”
Section: Theoretical Implicationssupporting
confidence: 90%
“…As a result, consumers may place greater value on cleanliness and sanitation and behave in a risk-averse way to avoid health risks. This is consistent with the salience theory of choice under risk (Bordalo et al, 2012;Bordalo et al, 2013) and more recent COVID-19 studies which confirmed that safety has become customers' primary concern (Chang and Cheng, 2022;Kim et al, 2021a). Therefore, this study confirmed the effectiveness of the salience theory under risk in understanding consumers' restaurant choice amid a global pandemic.…”
Section: Theoretical Implicationssupporting
confidence: 90%
“…Since the individuals would not use the ICT devices and system, the questionnaire was mostly answered by the relatives, but there were still some residents who could answer the questionnaire by themselves. The PZB is a multi-dimensional instrument designed for evaluating user expectations and perceptions of services [ 22 , 23 , 24 ]. Five dimensions—tangibles, reliability, responsiveness, assurance, and empathy—form the SERVQUAL measure and are used to characterize service quality [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The data can be uploaded to the cloud such that relatives can monitor the biometric values of the residents anytime and anywhere, and interactive cloud healthcare management can be established. The use of the modified service agreement model PZB [ 22 , 23 , 24 ] to conduct a questionnaire for residents, residents’ relatives, and caregivers about heath monitoring, chronic disease, and drug safety before/after the incorporation of the system. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hosts’ service quality attributes show the service quality provided by the hosts, such as 90-day availability, host identity verified, host since and host listings count (Xie and Mao, 2017). These service quality attributes can directly reflect the host’s commitment to the quality of homestay services (Xie and Mao, 2017; Chang and Cheng, 2022), which influence room sales (Xie and Mao, 2017). Although some studies have explored the impact of a single information signal/cue or the impacts of different cue combinations on various factors on P2P platforms (Filieri et al , 2020; Xie et al , 2021; Sainaghi et al , 2021), it remains unclear how online ratings and hosts’ service quality attributes affect sales on P2P platforms.…”
Section: Introductionmentioning
confidence: 99%